Libreoffice impress como herramienta metodológica para potenciar el aprendizaje del vih/sida y sífilis, con los estudiantes de décimo grado de educación general básica, del colegio de bachillerato Manuel Enrique Rengel de la ciudad de Loja, período 2014-2015 - Silva Viñamagua, Diego Vinicio (2016)
This research aims to publicize the importance of information and communications technology (ICT) and methodological tools to better develop the teaching-learning process by providing students the acquisition of knowledge in a more dynamic way and creative. In addition, ICT constitute methodological tools that favor the teaching-learning process in schools that do not have a library or sufficient teaching materials. These technologies allow entering a new world full of information, easy access for teachers and students. Similarly, they recreate the atmosphere of learning and cognitive development allows creative and fun way traditional curriculum areas. During the learning process several methodological tools for teaching is used, these are used empirically sometimes incompletely; ignorance and / or lack of training in the use of the same, hence it is very important to study, analyze and implement the various concepts, theories and methodologies for the proposed objectives are achieved. In this context, for this investigation the following issue was raised: "LIBREOFFICE IMPRESS AS A TOOL TO ENHANCE LEARNING HIV / AIDS and syphilis WITH TENTH GRADE STUDENTS GENERAL EDUCATION BASIC SCHOOL HIGH SCHOOL “MANUEL ENRIQUE RENGE " LOJA CITY, PERIOD 2014-2015” The general objective was raised: Use the " LibreOffice Impress as a methodological strategy to strengthen learning on HIV/ IDS and syphilis, with sophomores of basic general education school high school " Manuel Enrique Rengel " period 2014- 2015. The methods used were: deductive and inductive analytical-synthetic, which served to present, compare and interpret data logically from literature sources such as books, websites, magazines and documents; in addition to select, elaborate and synthesize the empirical information obtained from the current situation in order to investigate. To obtain the information was used as a technique and as the survey instrument, the questionnaire, the literature technique for lifting the theoretical framework (literature review). We worked with 12 students was the tenth year population, parallel “A" With the analysis, discussion and interpretation of the data obtained it evidenced that students do not have a clear understanding about HIV/AIDS and syphilis; also the teacher of Natural Science teaches classes in a traditional way, where everything is theoretical and the student must memorize the information provided to the letter without analyzing or understanding; reaching a limit, in which classes become tiresome and boring, the lack of technological tools and the lack of methodologies and teaching strategies. LibreOffice Impress implemented the program with the above subject, clearly showed that students were able to assimilate, understand and translate the information into their cognitive structure, yielding positive results in the implementation of the post-test. Given this we can say that the software LibreOffice Impress is important to carry out the teaching-learning process.